CASE STUDY ON ANOMALY OF ROTOR DYNAMIC VIBRATION SYMPTOM SYSTEM USING ANSY - AULIA (NIM : 13105046); Pembimbing : Prof. Dr. Ir. Indra Nurhadi, DEDI
Critical speed is one of the important factors in operation of rotor dynamic systems. Finite Element Methods (FEM) frequently used as alternative option in analyzing rotor dynamic systems, due to its cost is relatively cheap and the results of the system modelling often represent the actual system finely. On these final project, it is discussed about a case study of an eight stages compressor with anomaly appearances in its vibration symptoms. Normally, if a rotor dynamic system vibrates at the level out of the allowed range, the operation speed will decreased by operator and vibration level decreases as well. But in these case, while the operation speed decreased, in contrary the vibration level increases. Based on field operation data, hypotheses about the source of the problem made; there are transition of operation range between two critical speeds and bearing malfunctions. Then the system was modeled and analyzed by using ANSYSÃ‚Â™ software to prove the hypotheses. Software modelling results showed that the vibration symptoms in the model is similar the actual system as the modeshape of the system changed. Then it is analyzed and concluded that the sources of vibration anomaly is malfunction of the bearing which its stiffness decreased, in agree with the hypotheses created before.